Case Report: A Case of Hereditary Gingival Fibromatosis With a High Level of Human β Defensins in Gingival Epithelium - Gao, Ge; Tian, Qing; Han, Anpeng; Yang, Rongxia; Shi, Fan; Chen, Dong (Frontiers in Immunology, 2021)
Hereditary gingival fibromatosis (HGF, [MIM 135300]), a rare benign oral condition, has several adverse consequences such as aesthetic changes, malocclusion, speech impediments, and abnormal dentition. However, relatively few studies have addressed the beneficial effects of thick gingival tissues in resisting external stimuli. In this report, we present a unique case of a family affected by HGF that manifests as a ‘healthy’ gingiva. Human β-defensins (hBDs) are known to play a pivotal role in the clearance and killing of various microbes, and contribute to maintaining a healthy oral environment, which is currently emerging research area. However, the expression pattern and localisation of hBDs in patients with HGF have not yet been reported. hBD-2 and hBD-3 in the pedigree we collected had relatively elevated expression. High hBD levels in the gingival tissue of patients from the family may be beneficial in protecting oral tissue from external stimuli and promoting periodontal regeneration, but their role and the mechanisms underlying HGF need to be clarified.